Modules and Bounded Linear Operators - Jasim, Muna; Ali, Manal (Al-Nahrain Journal of Science, 2018)
An associated R-module of T, which is denoted by V_(T,T^* ) is given, Where V is an inner product space and T is bounded linear operator on V. We study in this paper properties of T which effects V_(T,T^* ) and conversely.